Current Issues of Safety and Quality of In-home Medical Care Provided to Adult Population - N. E. Parsadanyan; A. M. Kuznetsova (Здоровье мегаполиса, 2025)
Introduction. Taking into account the growing number of elderly people and patients with chronic diseases, an increase in the volume of in-home medical services requires special attention to quality and safety issues. Medical care provided at home should meet strict standards and protocols. Assessment of the quality of services should be carried out by means of  feedback systems and regular audits, thus improving the interaction between medical staff and patients. The study also examines the need for a multidisciplinary approach to medical staff training and the creation of interdisciplinary teams to ensure effective care.The purpose of the study was to analyze the existing models of in-home medical care provision, to identify their advantages and disadvantages, as well as to search for optimal ways to improve the quality and safety of the service provided to the adult population.Materials and methods. In this study, a variety of methodological approaches covering theoretical data analysis were used. Firstly, a literature review analyzing the existing studies and articles on safety and quality of in-home medical care provided to adult patients was conducted. Analytical methods were used for the ordering and further study of the collected data. An abstract and logical approach was used for the logical generalization of materials and the formation of reasoned conclusions.Results. To improve the quality and safety of in-home medical care provided to the adult population, it is necessary to introduce new work models. The first recommendation refers to the creation of integrated teams that will bring together specialists of various specialties. This will enable the consideration of complex medical and social aspects during the provision of medical care. Another important aspect is the introduction of telemedicine technologies that can significantly improve the accessibility and responsiveness of medical care. Telemedicine will help not only in organizing doctors’ meetings but also in ensuring constant monitoring of patients' conditions. The third recommendation is related to the improvement of the system of training and advanced training of medical professionals. This can be achieved by creating modular training programs that take into account the latest medical achievements and the specific characteristics of various categories of patients.